POPULATION AGEING IN BANGLADESH AND ITS IMPLICATION ON HEALTH CARE - Kabir, Russell; T.A.Khan, Hafiz; Kabir, Mohammad; Rahman, M Twyeafur (European Scientific Journal, ESJ, 2013)
In Bangladesh as in other regions of the world, the population ages 60 years and older is growing faster than the total population. Growth in the elderly population relative to other age groups challenges existing health services, family relationships and social security. With continued population ageing, the loss of cognitive function will potentially cause enormous social and economic burden on families, communities and, to the country. Using the census and secondary data, the paper investigates that increasing longevity and declining fertility are combining to convert the population age structure from young to old. This combination is resulting implications on the family health care and unmet need of health care services in the public sector. The support index shows that there will be fewer persons to support elderly population in future with implications in traditional family care. The care index shows the cost of burden for long term care associated with the shift in the population age structure. As a consequence Bangladeshi societies will confront population aging without traditional kin support.